The Verbal Violence of Indonesian Political Elites: A Deconstructive Analysis of Power in the Post-Truth Era - Mohammad Fikri; Suharijadi, Didik; Samson, Nur-Aida Tahirulla (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The phenomenon of violent speech among Indonesian political elites increased significantly during the post-transition regime period of 2024, particularly on digital platforms that amplify the visibility of controversial discourse. This study aims to identify the linguistic patterns of verbal violence employed by political elites and to explain how these language strategies contribute to the construction of power relations in the post-truth era. The research adopts a corpus-based critical discourse analysis with Derrida’s deconstruction as its theoretical lens. The data consist of 142 public statements drawn from political speeches, media interviews, press releases, and posts on TikTok, X, and YouTube between January and July 2025. The analysis was conducted in three stages: corpus mapping using AntConc, thematic coding with NVivo, and binary opposition deconstruction to uncover symbolic strategies. The findings reveal three main categories of verbal violence: (1) mockery and personal insults through bodily metaphors and vulgar diction, (2) group stigmatization such as the dichotomy of “ordinary people” versus “global elites,” and (3) symbolic threats grounded in moral and religious legitimacy. These linguistic strategies are further reinforced by social media algorithms that prioritize provocative content, thereby shaping public opinion and deepening political polarization. This study contributes to the development of political linguistics in Indonesia by highlighting the interconnection between elite discourse, algorithmic amplification, and the construction of power within the post-truth context.